SYNERGY OF WORK DISCIPLINE AND PHYSICAL WORK ENVIRONMENT: EMPLOYEE PERFORMANCE TRANSFORMATION AT PT. PANRAMA VISTA GARMENT INDUSTRY - Sunarto, Ading; Septiani, Nunki (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The purpose of this study was to determine the implementation of Work Discipline Synergy and Physical Work Environment at PT. Panrama Vista Garmen Industri. The method used is qualitative. The method used is a descriptive qualitative approach, which is a research method used to research natural object conditions, where the researcher is the key instrument. Data collection techniques used are triangulation or combined. Data were collected by observation, interviews, documentation. Data analysis through data reduction, data presentation, drawing conclusions or verification. where the goal is to systematically find out about the focus of the study. The results of the study indicate that the application of work discipline synergy and the physical work environment shows quadrant I "Progressive/Growth" which indicates that the company/organization has great potential to develop and improve its performance. The application of Work Discipline and Physical Work Environment can produce maximum performance levels if the company's employee needs are supportive and adequate